AiREAS: Sustainocracy for a Healthy City: Phase 3: Civilian Participation - Including the Global Health Deal Proposition - Close, Jean-Paul (SpringerBriefs on Case Studies of Sustainable Development, 2016)
Development Economics, Atmospheric Protection / Air Quality Control / Air Pollution, Urban Studies/Sociology, Social Choice/Welfare Economics/Public Choice, Group Theory and Generalizations, Data Mining and Knowledge Discovery